Pd(II)−Catalyzed Non‐Directed Benzylic C(sp3)−H Activation: Cascade C(sp3)−S Bond Cleavage to Access Benzaldehydes from Benzylphenyl Sulfides and Sulfoxides. Issue 12 (12th September 2022) - Joshi, Asha; Iqbal, Zafar; Kandwal, Pankaj; De, Saroj Ranjan
Abstract: A novel, efficient and mutual strategy on Pd(II)−catalyzed inert benzylic C(sp 3 )−H bond activation of benzylphenyl sulfides and sulfoxides has been developed that provides access to a series of benzaldehydes via cascade C(sp 3 )−S bond cleavage in one pot. The highlight of this protocol is the regiospecific activation of less reactive benzylic C(sp 3 )−H bond as compared to heteroatom‐directed more reactive C(sp 2 )−H bond, thus providing a strategy for late−stage site−selective C(sp 3 )−H bond functionalization. The reaction proceeds under air in moderate to good yields with excellent functional groups tolerance. Abstract : Palladium(II)−catalyzed inert benzylic C(sp 3 )−H bond activation of benzylphenyl sulfides and sulfoxides has been developed that affords a series of benzaldehydes via cascade C(sp 3 )−S bond cleavage in one pot under a mutual conditions. This provides a strategy for late–stage site–selective C(sp 3 )–H bond functionalization via regiospecific activation of less reactive benzylic C(sp 3 )–H bond as compared to heteroatom–directed more reactive C(sp 2 )–H bond. The catalyst is recycled under aerobic condition.